Localisation of a gene causing endocrine neoplasia to a 4 cM region on chromosome 1p35-p36. Issue 8 (August 1997) - Williamson, C; Pannett, A A; Pang, J T; Wooding, C; McCarthy, M; Sheppard, M N; Monson, J; Clayton, R N; Thakker, R V
Abstract : The development of some endocrine tumours, such as medullary thyroid carcinomas, phaeochromocytomas, anterior pituitary adenomas, and parathyroid adenomas involve a putative tumour suppressor gene located on chromosome 1p32-pter, a region that represents 111 cM. In order to refine the location of this gene, 93 endocrine tumours (39 parathyroid adenomas, 40 anterior pituitary adenomas, seven pancreatic islet cell adenomas, and seven carcinoids) were investigated for loss of tumour heterozygosity (LOH) using the seven polymorphic loci 1pter-D1S228-D1S507-D1S234-D1S476-D1S22 0-D1S207-D1S206-1cen. LOH was detected in 27% of the parathyroid tumours and in 7.5% of the pituitary tumours, but in none of the pancreatic islet cell or carcinoid tumours. In addition, seven of the 10 parathyroid tumours that showed LOH of chromosome 1p facilitated a more precise mapping of this putative tumour suppressor gene; five tumours involved a loss only of the telomeric locus D1S228, whereas two other tumours showed LOH at the centromeric loci D1S507, D1S234, D1S476, and D1S220, but not D1S228. Thus, our results have mapped this tumour suppressor gene implicated in endocrine tumours to a 4 cM region flanked by D1S228 and D1S507 on chromosome 1p35-p36.